PHP for Absolute Beginners - Lengstorf, Jason (Apress, 2012)
This book is the book I wish I’d had when I first started programming. It assumes no knowledge of PHP, but it doesn’t spend hundreds of pages on programming theory or the history of the language. Sure, it covers that, but what I really wanted to do was jump right in and teach you how to build something that you could use. I chose a blogging application because it feels like everybody has a blog these days, and why shouldn't you know how to build one? In this book, I've tried to write exactly the way I’d teach you one-on-one: you should feel comfortable with what’s being discussed, but not bored. The material should move quickly, but remain easy-to-follow. I also want you to feel like you're learning, not memorizing. And most importantly, when you’ve finished this project, I want you to turn around and build another one – this time without any help. PHP is a great language, and it provides developers with the ability to build pretty much anything they can imagine when paired with a database and some good ol’ HTML. However, it can also seem intimidating. It’s not visual like front-end design, there’s all this theory involved, and it’s just, you know, harder. But that doesn’t have to be the case, and it’s my sincere hope that this book will allow you to get your hands dirty with PHP without ever feeling intimidated, lost, or hopeless. It wasn't long ago that I was struggling through complex, boring how-tos on PHP, so I know how it is to feel completely overwhelmed by the massive amounts of information about the language. It's my sincere hope that I've written a book that will allow you to learn everything you need to know in a far less stressful manner. So take a deep breath and turn the page. Let's do this!